Amorphous TiO2-Au thin film composites synthesized by pulsed laser deposition (Superficies y Vacío, 2023)
TiO2 has been widely studied and synthesized by various methods due to its excellent optoelectronic properties. It is possible to modify the optical properties of TiO2 by incorporating noble metal nanoparticles in order to improve its photoresponse. In this work, TiO2-Au thin film composites were grown by pulsed laser deposition technique. Ti and Au targets were simultaneously ablated in order to produce combined plasmas under a reactive atmosphere containing oxygen at a pressure of 2×10-2 Torr. The plasmas were analyzed individually by means of a planar Langmuir probe in order to calculate their mean kinetic ion energy and plasma density. Ti plasma parameters were kept constant at 196 eV and 2.06×1013 cm-3 while the Au plasma density was varied from 2.65×1012 cm-3 to 22.4×1012 cm-3. The samples were characterized by UV-Vis spectroscopy and scanning electron microscopy.  The band gap of the films was determined by means of the Tauc method, which decreased from 2.36 to 1.54 eV as the Au plasma density increased. The resultant morphology of the films shows the formation of spherical Au nanoparticles, whose average sizes increases as the Au plasma density increased, resulting in values ranging from 15 to 72 nm.